2022
DOI: 10.3390/life12121982
|View full text |Cite
|
Sign up to set email alerts
|

Origanum majorana Essential Oil—A Review of Its Chemical Profile and Pesticide Activity

Abstract: Origanum majorana is a medicinal and aromatic plant that belongs to the Lamiaceae family. It is cultivated in several parts of the world and, due to its splendid aroma and taste, is widely used for culinary purposes and in perfumes. The essential oil of the plant, to which is attributed its aroma, contains many secondary metabolites with valuable biological activity. One of them is the pesticide activity, which has attracted much interest. Given the necessity of replacing synthetic pesticides, essential oils a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…OEOV effects on sporangia release, zoospore mobility or germination are likely also contributing factors for the direct effect on P. viticola sporangia but were not investigated in the present study. Several studies show the direct antimicrobial, insecticidal and antifungal activity of origanum essential oils in different 21 , 38 plant and mammals 21 , 38 ; thus far, only one published study showed that essential oil vapour has a phenotypic effect on P. viticola post-inoculation 20 . OEOV acted in a time- and duration-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OEOV effects on sporangia release, zoospore mobility or germination are likely also contributing factors for the direct effect on P. viticola sporangia but were not investigated in the present study. Several studies show the direct antimicrobial, insecticidal and antifungal activity of origanum essential oils in different 21 , 38 plant and mammals 21 , 38 ; thus far, only one published study showed that essential oil vapour has a phenotypic effect on P. viticola post-inoculation 20 . OEOV acted in a time- and duration-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…These include, among others, the application of natural substances, such as sage extracts 7 , chitosan 8 , other diverse plant extracts, different bacteria 9 , dsRNA 10 , sulfated laminarin/PS3 11,12 , BTH (Benzothiadiazole), methyl jasmonate, PHOS (phosphonates) 13 , peptide NoPv1 14 , BABA (β-aminobutyric acid) 15 , kaolin 16 , d-Tagatose 17 , Trichoderma harzianum 18 or Cerevisane 19 . Essential oils from the Lamiaceae family 20 , such as Origanum vulgare, is a particularly promising natural product whose direct action on numerous pathogens has already been demonstrated [20][21][22] . It has also been found to be very efficient in trials conducted in climate chambers on grapevine 23,24 .…”
mentioning
confidence: 99%
“…M. spicata has several biological uses thanks to the abundance of carvone, a potent monoterpene able to suppress fungal disease and the sprouting of stocked foods [ 88 ]. M. hortensis contains many secondary metabolites, terpenes predominantly, with valuable biological activity; considerable studies have demonstrated its pesticide activity [ 89 ]. Finally, it is possible to affirm that EOs derived from plants belonging to the Lamiaceae family are the most investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Plant essential oils are the main source of aromatic plant odors, which are mainly derived from the roots, stems, leaves, and other organs of plants and have long been used in culinary and medical applications in the historical record [6]. With deeper research, it has been found that plant essential oils have excellent antioxidant activity, antimicrobial activity, and other biological activities [7], which are mainly derived from the constituents of plant essential oils, which are dominated by terpenes and phenyl terpenoids, of which monoterpenoids are the most common [8] and, thus, natural compounds have been incorporated into the study of natural antimicrobial substances.…”
Section: Introductionmentioning
confidence: 99%